SISTEM PENGOLAHAN LIMBAH CAIR TAPIOKA DI PT X - Alif Maulana Al Hussain; Natalina Natalina; Nasution Nasution (KAMPUS AKADEMIK PUBLISING, 2026)
The tapioca starch processing industry produces liquid waste with high organic content, such as BOD, COD, TSS, oil and fat, cyanide, and ammonia. If not managed properly, this liquid waste has the potential to pollute the environment and disrupt the quality of aquatic ecosystems. PT X is one of the tapioca industries in Lampung that produces large amounts of liquid waste, requiring an effective waste treatment system. The treatment system used is a wastewater treatment plant (WWTP) using anaerobic, facultative, and aerobic methods. Based on laboratory test results, the levels of BOD, COD, TSS, pH, cyanide, oil and fat, and NH₃-N decreased significantly after going through the processing process and have met the quality standards stipulated in the Minister of Environment Regulation No. 5 of 2014. Thus, the WWTP system is considered to be functioning well, although it still requires regular monitoring and maintenance to maintain optimal performance.